2023
DOI: 10.1186/s13756-023-01208-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the implementation of WHO infection prevention and control core components in Turkish health care facilities: results from a WHO infection prevention and control assessment framework (IPCAF)—based survey

Abstract: Background The core components (CCs) of infection prevention and control (IPC) from World Health Organization (WHO) are crucial for the safety and quality of health care. Our objective was to examine the level of implementation of WHO infection prevention and control core components (IPC CC) in a developing country. We also aimed to evaluate health care-associated infections (HAIs) and antimicrobial resistance (AMR) in intensive care units (ICUs) in association with implemented IPC CCs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Furthermore, this study is inconsistence with other studies done in Turkish health care facilities which indicated a total of 68 HCFs from seven regions in Turkey and the Turkish Republic of Northern Cyprus. 50 (73.5%) HCFs had advanced IPC levels, while 16 (23.5%) of hospitals had intermediate IPC levels [14].…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, this study is inconsistence with other studies done in Turkish health care facilities which indicated a total of 68 HCFs from seven regions in Turkey and the Turkish Republic of Northern Cyprus. 50 (73.5%) HCFs had advanced IPC levels, while 16 (23.5%) of hospitals had intermediate IPC levels [14].…”
Section: Discussionmentioning
confidence: 97%
“…The median IPCAF score varies from ‘inadequate IPC level’ in Pakistan [ 17 ] to an advanced level obtained from Germany, Turkey, India, Austria, and Indonesia. In addition, a difference exists within the eight core components [ [12] , [13] , [14] , 18 , 20 , 21 ]. The IPCAF of each core component showed a low mean value in Pakistan [ 16 ] compared with Austria [ 20 ] as shown in Figure 2 .…”
Section: Discussionmentioning
confidence: 99%
“…A higher median IPC score was recorded in Turkey and India [ 12 , 14 ] compared with Bangladesh [ 22 ] in each of the IPCAF core components. The higher score obtained from Turkey may be due to the higher income level and more attention given to IPC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results cannot be generalized for geographical areas with a high prevalence of carbapenemases, and further studies are required, with important implications for stewardship or preventive strategies. The implications for antimicrobial stewardship or VAP prevention are beyond the scope of this article, and we refer the readers to recent updates [ 2 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 ] addressing these important issues.…”
Section: Discussionmentioning
confidence: 99%